A critique of Pine’s construction theory of “Shanrang” in the Zhan Guo period from a historical writing perspective - Zhang, Yi (Thai Journal of East Asian Studies, 2024)
Yuri Pines once proposed that shanrang (abdication) was a construction of the Zhanguo (Warring States) period, about 475 BCE to 221 BCE, and regarded shanrang as the historical invention of political thinkers of that era, especially equalitarians, rather than existing as a system in history. This article attempts to reexamine this viewpoint by existing literature in relevant fields (whether traditional Chinese books or the literature), and combining concepts, theories, and methods of history writing to comprehensively scrutinize the shanrang narrative in traditional Chinese history books, to discern whether and how shanrang should exist in history. After pinpointing shanrang’s place in history as an historical process, Pines’ theory was critically evaluated. The validation of this approach innovates in discussing ancient Chinese systems while revealing limitations in the shanrang construction theory during the Zhanguo period. These include an innately negative attitude about the existence of the shanrang system, and theoretical issues requiring attention that should inspire innovative thematic study of sinology.